Cross-cultural validation of the Cebuano version of a screening questionnaire for Parkinson's disease - Dakay, Daryl; Tangcalagan, Faith; Villanueva III, Emilio; Abejero, Joshua; Saranza, Gerard; on behalf of the Philippine Parkinson's disease Prevalence Study Group (Arquivos de Neuro-Psiquiatria, 2022)
Background In the Philippines, the exact prevalence of Parkinson's disease (PD) has not yet been determined. Although cases can be extrapolated from medical registries, this method may undermine actual case rates. A reliable screening tool for PD is essential for a timely diagnosis and community-based epidemiological studies. The most widely used screening questionnaire for PD diagnosis was developed by Tanner et al., which consists of nine questions about the motor symptoms of PD. Although this questionnaire has been translated to several languages, the translated version must be validated for use in our local setting.Objective To determine the validity of the Cebuano version of a PD screening questionnaire.Method The questionnaire was translated from English to Cebuano by a hired language specialist. Each item was supplied with a yes, no, or don't know answer. A total of 73 patients with PD and 244 control subjects completed the study.Results The overall Cronbach alpha for internal consistency of the questionnaire was 0.9410. The item on tremor had the highest sensitivity (97.26%), while the item on problems with buttoning had the highest specificity (100.00%). A cut-off score  ≥ 3 obtained the best Youden index (99.18%), with a sensitivity of 100.00% and a specificity of 99.18%. The questionnaire had an almost perfect predictive ability to diagnose PD (AUC of 0.9994).Conclusion The translated version of the Tanner questionnaire is a validated instrument to identify PD in a literate Cebuano population.
Keywords: Parkinson Disease; Philippines; Epidemiology